Overview of blended learning: the effect of station rotation model on students’ achievement - Ayob, Nur Fathin Suhana; Abd Halim, Noor Dayana; Zulkifli, Nurul Nadwa; Mohd Zaid, Norasykin; Mokhtar, Mahani (Advanced Scientific Research, 2020)
This paper aims to review on blended learning models specifically on station rotation model includes the implementations and results of past studies on students’ achievement. This paper starts with an overview of blended learning concepts that could be implemented in teaching and learning and the issue arising in the promoting better understanding of the concepts. The discussion leads to the potential of using a station rotation model of blended learning for future study as the review from the past studies revealed that this model had positive impacts on students' achievement. These results are so promising, and this model could be designed and implemented in future studies.